Combined effects of temperature and copper and S-metolachlor on embryo-larval development of the Pacific oyster, Crassostrea gigas. (15th February 2017) - Gamain, Perrine; Gonzalez, Patrice; Cachot, Jérôme; Clérandeau, Christelle; Mazzella, Nicolas; Gourves, Pierre Yves; Morin, Bénédicte
Abstract: This study evaluates the combined effects of two contaminants (copper and a herbicide S-metolachlor) and temperature on the early life stages of the Pacific oyster Crasssotrea gigas, which is native to Arcachon Bay (southwest France). The responses of D-larvae, obtained from wild and cultivated oysters, were investigated for one year during the oyster breeding period at different sampling sites and compared with the response of D-larvae from a commercial hatchery. Embryotoxicity was measured by considering the percentage of abnormal D-shaped larvae. Normal development of embryos occurred only from 22 °C to 26 °C. There were synergistic effects of copper at low and high temperatures. Native oysters appear particularly sensitive to an increase in water temperature, suggesting a future increase in the percentage of larval abnormalities as a result of global climate change. Hatchery oysters represent a good alternative model for studying the effects of both pollutants and climate change stressors. Graphical abstract: Highlights: Oyster embryos were exposed to copper, S-metolachlor and different temperatures. Environmental concentrations of copper and a herbicide impair D-larvae development Embryo-larval development is affected at low and high temperature. Synergistic effects of copper at low and high temperature Embryos from hatchery or from the field display the same sensitivity to pollutants.